Coexistence of vascular Ehlers-Danlos syndrome and sticky platelet syndrome: a lethal combination in a young patient with thrombophilia and haemorrhagic diathesis - Manuel De Miguel-Escribano; Manuel Garrido-Montes; Pablo Astudillo-Ortega; Roberto Pertusa-Mataix; Andrea Rodríguez-Trigueros; Jorge Corchero-Gijón; Jose-Salvador Garcia-Morillo (European Journal of Case Reports in Internal Medicine)
Background: The coexistence of hypercoagulability and bleeding diathesis in the same patient represents a potentially lethal combination due to its complex management. Vascular Ehlers-Danlos syndrome (vEDS) and sticky platelet syndrome (SPS) are classified as rare diseases due to their low prevalence. vEDS is associated with bleeding tendencies caused by vascular wall fragility, while SPS is characterized by atypical arterial and venous thrombosis. Case Report: We report a 27-year-old woman, smoker and regular consumer of energy drinks, with a medical history of subclinical hypothyroidism, minor thalassemia, recurrent joint sprains, high myopia, and anterior mitral valve prolapse, who was diagnosed with both vEDS and SPS type I. The patient experienced a catastrophic progression over a short time period, marked by numerous thrombotic and bleeding episodes, ultimately leading to a fatal outcome. Conclusions: This report documents the first known case of concurrent vEDS and SPS, highlighting the complexity and challenges in the management of these two rare conditions together. The interplay between these syndromes necessitates careful clinical consideration and the development of tailored management strategies to mitigate associated risks. This underscores the crucial role of the internist in overseeing such cases. Further studies are needed to explore new therapeutic strategies aimed at improving survival rates and outcomes for patients with this unique combination of disorders.